Pharmacare 2025: a platform for community engagement and professional development - Mohd Rizalmi, Intan Rynn Zulaikha; Ismail, Farhana Fakhira (Faculty of Pharmacy, 2025)
The PharmaCare program concluded successfully on 11 January 2025. Organised as a collaborative initiative between final-year students enrolled in PHC670 and those undertaking PHC665 (Know Your Medicine), the event was held at the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam. The programme attracted members of the public and served as an avenue for students to engage with the community while enhancing their professional competencies.